Secretory Vesicles Targeted to Plasma Membrane During Pollen Germination and Tube Growth - Ruan, Huaqiang; Li, Jiang; Wang, Ting; Ren, Haiyun (Frontiers in Cell and Developmental Biology, 2021)
Pollen germination and pollen tube growth are important biological events in sexual reproduction of higher plants, during which a large number of vesicle trafficking and membrane fusion events occurred. When the secretory vesicles are transported via the F-actin network in proximity to the apex of pollen tube, the secretory vesicles are tethered and fused to the plasma membrane by tethering factors and SNAREs proteins, respectively. The coupling and uncoupling between the vesicle membrane and plasm membrane are also regulated by dynamic cytoskeleton, proteins and signal molecules including small G proteins, calcium and PIP2. In this review, we will focus on the current knowledge of the secretory vesicle delivering, tethering and the fusion during pollen germination and tube growth, and also summarize the progress how the regulators and signaling molecules take participate in the above process.